Evaluation of Medium Chain Fatty Acids as a Dietary Additive in Nursery Pig Diets - J. T. Gebhardt; K. A. Thomson; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 360 pigs [DNA (Columbus, NE) 400 × 200; initial BW = 14.8 lb] were used to evaluate the effects of dietary medium chain fatty acid (MCFA) addition on nursery pig performance. Upon arrival to the nursery, pigs were randomized to pens (5 pigs per pen) and allowed a 6-d acclimation period, at which point pens of pigs were blocked by BW and randomized to dietary treatment (9 pens per treatment). Medium chain fatty acids (Sigma Aldrich, St. Louis, MO) included hexanoic (C6), octanoic (C8), and decanoic (C10), and were guaranteed ≥ 98% purity. Treatment diets were formulated and manufactured in two dietary phases (dietary phase 1 = 15 to 25 lb BW; dietary phase 2 = 25 to 50 lb BW) and were formulated to meet or exceed NRC requirements. Treatments (n = 8) were constructed such that a dose response was created including 0, 0.25, 0.5, 1.0, and 1.5% MCFA blend (1:1:1 ratio C6, C8, and C10) as well as treatments with either 0.5% C6, 0.5% C8, or 0.5% C10. During phase 1, pigs fed increasing MCFA blend had increased (linear, P ≤ 0.003) ADG and ADFI, as well as improved F/G (quadratic, P = 0.012). Pigs fed 0.5% C6 and 0.5% C8 had greater (P ≤ 0.018) ADG than pigs fed the control diet without MCFA. Pigs fed 0.5% C8 had greater ADFI than control fed pigs (P = 0.023), and pigs fed 0.5% C6, 0.5% C8, or 0.5% C10 had improved F/G (P ≤ 0.005) compared to control fed pigs. Pigs fed 0.5% C8 had a marginally significant increase (P = 0.094) in ADFI compared to pigs fed 0.5% blended MCFA. Pigs fed 0.5% C10 tended to have poorer (P = 0.060) F/G compared to pigs fed the 0.5% MCFA blend diet. During phase 2, ADG increased (linear, P = 0.007) and ADFI marginally increased (linear, P = 0.052) with increasing MCFA blend. Pigs fed 0.5% C10 had marginal improvement (P = 0.079) in F/G compared to control fed pigs. Overall, ADG and ADFI were increased (linear, P ≤ 0.01) and F/G improved (linear, P = 0.004) with increasing MCFA blend. Pigs fed 0.5% C6 or 0.5% C8 had greater (P ≤ 0.027) ADG compared to pigs fed the control diet, and F/G was improved (P ≤ 0.003) when pigs were fed 0.5% C6, 0.5% C8, or 0.5% C10 compared to control. In summary, adding a blend of MCFA in nursery pig diets led to linear improvement in ADG, ADFI, and F/G. Thus, the use of MCFA products in nursery pig diets offers a significant potential to improve growth performance and economic return to swine producers. Additional research is warranted to determine if commercially available products have a favorable MCFA profile, and if such products yield similar advantages in growth performance and economic return.
Keywords: medium chain fatty acid; nursery pigs